2020
DOI: 10.1051/0004-6361/201936990
|View full text |Cite
|
Sign up to set email alerts
|

The origin of tail-like structures around protoplanetary disks

Abstract: Aims. We study the origin of tail-like structures recently detected around the disk of SU Aurigae and several FU Orionis type stars. Methods. Dynamic protostellar disks featuring ejections of gaseous clumps and quiescent protoplanetary disks experiencing a close encounter with an intruder star were modelled using the numerical hydrodynamics code FEOSAD. Both the gas and dust dynamics were taken into account, including dust growth and mutual friction between the gas and dust components. Only plane-of-the-disk e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…Additional multiple systems show signs of stellar interactions, such as tidal streams: FU Ori ( Tobin et al 2016;Alves et al 2019). The observed features are consistent with numerical predictions (Dai et al 2015a;Bate 2018;Cuello et al 2019;Vorobyov et al 2020) and offer laboratories to better understand the disk dynamics by quantifying their response to gravitational torques. In particular, the synergy of gas dynamics in spirals, and the distribution of small and large dust grains as traced by IR scattered light images and mm thermal emission, can lead to constraints on the coupling between gas and dust in disks, and on the thermal structure of the disk itself (Juhász and Rosotti 2018;Rosotti et al 2020a).…”
Section: Streamers Stellar Fly-bys and Tidal Interactionssupporting
confidence: 80%
“…Additional multiple systems show signs of stellar interactions, such as tidal streams: FU Ori ( Tobin et al 2016;Alves et al 2019). The observed features are consistent with numerical predictions (Dai et al 2015a;Bate 2018;Cuello et al 2019;Vorobyov et al 2020) and offer laboratories to better understand the disk dynamics by quantifying their response to gravitational torques. In particular, the synergy of gas dynamics in spirals, and the distribution of small and large dust grains as traced by IR scattered light images and mm thermal emission, can lead to constraints on the coupling between gas and dust in disks, and on the thermal structure of the disk itself (Juhász and Rosotti 2018;Rosotti et al 2020a).…”
Section: Streamers Stellar Fly-bys and Tidal Interactionssupporting
confidence: 80%
“…All three burst mechanisms were simulated using the same numerical hydrodynamics code FEOSAD 1 . A detailed description of the code is presented in Vorobyov & Elbakyan (2018), with modifications relevant for modeling the MRI bursts and close encounters in Kadam et al (2020) and Vorobyov et al (2020c), respectively. Here, we review only the key aspects of burst modeling.…”
Section: Model Description and Considered Burst Mechanismsmentioning
confidence: 99%
“…To study the bursts caused by close encounters, we use the model recently presented in Vorobyov et al (2020c). In this collision model, a diskless star is set on an encounter trajectory with a protoplanetary disk around a sub-solar mass star.…”
Section: Model Description and Considered Burst Mechanismsmentioning
confidence: 99%
“…Gravitational instabilities (GI), potentially precipitated by infalling material, may drive spiral arm formation as well as the formation of tail-like structures through gas clumps ejected when the disk fragments (e.g., Boss 1997;Gammie 2001;Vorobyov & Basu 2005;Kratter et al 2008;Harsono et al 2011;Vorobyov et al 2020). It is ambiguous from Toomre Q parameter estimates whether GM Aur is in fact unstable.…”
Section: Gravitational Instabilitymentioning
confidence: 99%
“…Simulations have shown that close stellar encounters can create spiral and tail structures in disks (e.g., Clarke & Pringle 1993;Pfalzner 2003;Cuello et al 2019;Vorobyov et al 2020). Gas structures reminiscent of the GM Aur system have also been detected in several systems with stars separated by projected distances of a few hundred au, including RW Aur A and B (Rodriguez et al 2018), AS 205 N andS (Kurtovic et al 2018), and UX Tau A and C (Zapata et al 2020).…”
Section: Other Explanationsmentioning
confidence: 99%